The Mediator complex subunit MoMed15 plays an important role in conferring sensitivity to isoprothiolane by modulating xenobiotic metabolism in M. oryzae - Fan-Zhu Meng; Wen-Kai Wei; Min-Zheng Cai; Zuo-Qian Wang; Liang-Fen Yin; Wei-Xiao Yin; Guido Schnabel; Chao-Xi Luo (mBio)
ABSTRACT Rice blast caused by Magnaporthe oryzae is one of the most economically important rice diseases. Fungicides such as isoprothiolane (IPT) have been used extensively for rice blast control, but resistance to IPT in M. oryzae is an emerging threat. In this study, molecular mechanisms of resistance in IPT-resistant mutants were identified. Through whole-genome sequencing and genetic transformation, we identified the gene MoMed15, encoding a transcriptional glutamine-rich co-activator Mediator complex subunit, in which mutations or deletion resulted in moderate IPT resistance. Further research found that MoMed15 physically interacted with the IPT resistance regulatory factor MoIRR to simultaneously regulate both MoIRR expression and the expression of multiple xenobiotic-metabolizing enzymes in response to IPT stress. We hypothesize that some xenobiotic-metabolizing enzymes enhance IPT toxicity by modifying the IPT structure. Variation of MoMed15 affected the recruitment of the transcriptional Mediator complex and decreased the expression of these xenobiotic-metabolizing enzymes, resulting in moderate IPT resistance. We also found that MoPGR1, encoding a protein that activates cytochrome P450 enzymes, was essential to confer IPT sensitivity, and its expression was directly regulated by MoIRR.IMPORTANCEIsoprothiolane (IPT) has been used extensively for the management of rice blast disease and IPT-resistant subpopulations have emerged in Chinese rice fields. The emergence of resistant pathogen populations has led to a steep increase in fungicide use, increasing pesticide risk for the applicator and the environment. The molecular mechanisms of IPT resistance in M. oryzae remain elusive. In this study, we demonstrated that transcriptional co-activator MoMed15 interacts with IPT resistance regulator MoIRR to recruit the Mediator complex, which promotes the expression of xenobiotic-metabolizing enzymes, leading to exacerbated IPT toxicity. The MoMed15 could be used for IPT resistance detection in rice fields.